Impact of induction on employee perceptions of health and safety at ArcelorMittal - Samosamo, Mothusi George (My University, 2015)
Workplace health and safety is a global concern. South African companies are bound by the stipulations of the Occupational Health and Safety Act (OHSA) (85 of 1993), which regulates employer and employee duties to identify and eliminate hazards, thereby controlling and minimising the risk to health and safety within the working environment. Employees are regarded as the strength of ArcelorMittal. The on-board programme of this employer is designed specifically to support the integration of new employees into ArcelorMittal’s environment and enable them to maximise their contribution to the performance of their team, implementation of a business plan and strategy and realisation of the group’s objectives. This study investigates the perceptions that ArcelorMittal (Vanderbijlpark) employees uphold regarding the effectiveness of the health and safety induction they received. The iron division was identified purposefully for selection of the target population because of its high rate of health and safety incidents. Simple random sampling was used within a quantitative research design to select 317 respondents out of 634 employees. Accordingly, questionnaires were distributed within the demarcated division and a total of 160 questionnaires were completed and returned. The collected data were statistically analysed and presented. The results indicated that the majority of employees perceive the health and safety induction they received to be effective. Respondents also indicated that ArcelorMittal was effective in providing them with the support they need towards their health and safety. Hence, it is recommended that the zero tolerance approach towards safety hazards be reinforced on a continuous basis within the work context of this leading steel manufacturer.
M. Tech. (Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Workplace health and safety; ArcelorMittal; 658.31244; Industrial safety -- South Africa.; Steel industry and trade -- South Africa.